Into the understanding the multicellular lifestyle of Proteus mirabilis on solid surfaces - Gmiter, Dawid; Kaca, Wieslaw (Frontiers in Cellular and Infection Microbiology, 2022)
Indwelling urinary catheterization can lead to the development of catheter-associated urinary tract infections (CAUTIs), an important type of nosocomial infection, as well as other medical issues among institutionalized adults. Recently, Proteus mirabilis was highlighted as the important cause of CAUTIs. The pathogenicity of P. mirabilis is dependent on two multicellular types of surface colonization: the adherence and swarming motility. Adhesion, mostly mediated by fimbrial and nonfimbrial adhesins, is important for the initiation of biofilm formation. Moreover, the production of urease frequently results in biofilm crystallization, which leads to the blockage of catheters. The heterologous polymeric matrix of the biofilm offers protection against antibiotics and the host immune system. P. mirabilis displays remarkable motility abilities. After contact with solid surfaces, hyper-flagellated cells are able to rapidly migrate. The importance of swarming motility in CAUTIs development remains controversial; however, it was indicated that swarming cells were able to co-express other virulence factors. Furthermore, flagella are strong immunomodulating proteins. On the other hand, both biofilm formation and swarming motility implicates multiple inter- and intraspecies interactions, which might contribute to the pathogenicity.